The application of phosphate solubilizing bacteria (PSB) in enhancing p availability from contaminated soil / Raja Nabira Raja Zulkifli - Raja Zulkifli, Raja Nabira (Faculty of Plantation and Agrotechnology, 2016)
The research was conducted on the application of Phosphate Solubilizing Bacteria (PSB), Baciluss Sinensis in enhancing P availability from contaminated soil due reduce the available P with increases level of heavy metals. The soil samples were obtained from paddy field at Merlimau, Melaka. The soil were contaminated with heavy metals such as copper sulphate and iron chloride and inoculated with Phosphate Solubilizing Bacteria (PSB). The media were planting with paddy the data was measured based of plant height and plant biomass. The total P was determine using wet digestion (Akinyle and Shokunbi, 2014) and available P were determine using Bray P method (Bray and Kurtz, 1945). From the result study shown that the application of PSB on different level heavy metals has no significances different in term soil pH, plant height of paddy, root biomass and tiller biomass. Meanwhile, for the result Total P, Available P, heavy metals content and root length shown that were significances different after inoculation of PSB with increasing level of treatment. In conclusion, it can be conclude that the application of PSB on contaminated soil can enhance the available P in the soil that making it much more available for the plant uptake.